In the Shadow of Djoser's Pyramid : Research of Polish Archaeologists in Saqqara. - Stępień, Miłosława. (Studies in Classical Literature and Culture Series, 2020)
Presentation of discoveries made by the Polish archaeological mission in Saqqara (Egypt) west of the Pyramid of Djoser, including cemeteries of noblemen form the Old Kingdom (the late third millennium BC) and the Ptolemaic Period (the late first millennium BC). Keywords: excavations, conservation, Old Kingdom, Ptolemaic Period, rock-hewn tombs.